(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
Motherhood is a concept that is shunned and criticised by Western feminists as one of the root causes of a woman’s subordination, dis-empowerment, lack of freedom and independence. It is also frowned at for binding her to what are considered as insignificant feminine duties linked to, and limited to the home, with her main arena being the kitchen. Other roles associated with being a mother, such as child-bearing, breast feeding and cooking are largely criticised as closing her out of mainstream economics and hence keeping her out of positions of influence and affluence. Using the theory of Africana Womanism and examples from Shona cultural milieu, the paper argues that being a mother is not only a very important and admirable position in this society, but one associated and intertwined with great power, respect, reverence among others.